Forgotten Chemo-Port Leading to Chylothorax: A Rare Presentation - Bajad, Pradeep; B, Avinash; Dutt, Naveen; Niwas, Ram; Garg, Pawan Kumar; Khera, Pushpinder; Chauhan, Nishant Kumar (Acta Biomedica Atenei Parmensis, 2022)
Chylothorax is an uncommon cause of pleural effusion in routine clinical practice. Thoracic surgery, trauma and malignancy are the leading causes of chylothorax accounting for more than 90% of cases.1,2 We report this rare case of a middle aged lady with treated carcinoma breast who presented with left-sided chylothorax secondary to subclavian vein and superior vena cava thrombosis caused by a longstanding indwelling chemo-port in the right internal jugular vein. Patient was managed on total parenteral nutrition (TPN) leading to complete resolution of chylothorax.